2010
DOI: 10.1007/s10773-010-0406-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Theory Approach for Neutron Single and Double-Slit Diffraction

Abstract: We provide a quantum approach description of neutron single and double-slit diffraction, with specific attention to the cold neutron diffraction (λ ≈ 20Å) carried out by Zeilinger et al. in 1988. We find the theoretical results are good agreement with experimental data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 17 publications
3
9
0
1
Order By: Relevance
“…It is shown that the results of our calculations are in good agreement with the experiments conducted by other groups. We have also compared our results to those of Xiang-Yao Wu et al [12] and good consistency was established. We have also used this method to model the electron diffraction.…”
Section: |supporting
confidence: 56%
See 3 more Smart Citations
“…It is shown that the results of our calculations are in good agreement with the experiments conducted by other groups. We have also compared our results to those of Xiang-Yao Wu et al [12] and good consistency was established. We have also used this method to model the electron diffraction.…”
Section: |supporting
confidence: 56%
“…M Beau has studied electron diffraction through slits analytically using the Feynman path integral [11]. Also Xiang-Yao Wu et al described neutron diffraction using a quantum approach considering the non-coherent quantum effect [12]. Their results were in good agreement with experimental results.…”
Section: |mentioning
confidence: 83%
See 2 more Smart Citations
“…Em [21], Xiang-Yao Wu et al examinam a difração de neutrons por uma e duas fendas com particular atenção para nêutrons frios. Aplicando a representação de Schrödinger em consonância com o teorema integral de Kirchhoff, eles encontraram duas expressões para a intensidade observada.…”
Section: Introductionunclassified